2017
DOI: 10.1016/j.hsag.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Adherence challenges encountered in an intervention programme to combat chronic non-communicable diseases in an urban black community, Cape Town

Abstract: Background: Chronic non-communicable diseases (CNCD) have become the greatest contributor to the mortality rate worldwide. Despite attempts by Governments and various non-governmental organisations to prevent and control the epidemic with various intervention strategies, the number of people suffering from CNCD is increasing at an alarming rate in South Africa and worldwide.Objectives: Study's objectives were to explore perceived challenges with implementation of, and adherence to health messages disseminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is possible that the recommendation for increased intake of healthy foods, for example, fruit and vegetables, disseminated in the FBTG sessions may have been difficult to implement by individual participants in our study sample. Love, Maunder and Green (2008) and Solomons, Kruger and Puoane (2017) reported in their qualitative research that some South African population groups consider fruit and vegetables as the more costly items to include regularly in a healthy diet. Temple and Steyn (2011) estimated that an additional R1090.00 per month would be required to cover the costs of healthier food items for a family of five, which is probably not achievable for the majority of participants in our sample who relied on a family income of less than R4166.66 per month.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the recommendation for increased intake of healthy foods, for example, fruit and vegetables, disseminated in the FBTG sessions may have been difficult to implement by individual participants in our study sample. Love, Maunder and Green (2008) and Solomons, Kruger and Puoane (2017) reported in their qualitative research that some South African population groups consider fruit and vegetables as the more costly items to include regularly in a healthy diet. Temple and Steyn (2011) estimated that an additional R1090.00 per month would be required to cover the costs of healthier food items for a family of five, which is probably not achievable for the majority of participants in our sample who relied on a family income of less than R4166.66 per month.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diseases associated with the heart, type 2 diabetes mellitus, some cancers and long-term infections of the respiratory system was reported as the primary cause of death globally in the past few decades (Habib & Saha 2010 ; Horton 2013 ; Nojilana et al 2016 , Solomons, Kruger & Puoane, 2017 ; Yuyun et al 2020 ). In the developed countries, it is reported that non-communicable diseases (NCDs), especially cardiovascular diseases (CVDs), were responsible for high rates of morbidity and mortality, resulting in 90% of all deaths (Yuyun et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having ample medical and pharmaceutical support, older adults still inevitably experience many complications in life and one of the most prevalent complications is chronic illness. The condition of chronic illness accounts for more than 50% of the global disease burden [ 5 ]. Chronic illness is the leading cause of death worldwide, accounting for 41 million deaths each year, equivalent to 71% of all deaths globally [ 6 ].…”
Section: Introductionmentioning
confidence: 99%